2021
DOI: 10.1101/2021.02.08.430277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning reveals cryptic dialects that guide mate choice in a songbird

Abstract: Culturally transmitted communication signals, such as human language or bird song, can change over time through a process of cultural drift, and may consequently enhance the separation of populations, potentially leading to reproductive isolation. Local song dialects have been identified in bird species with relatively simple songs where individuals show high cultural conformity. In contrast, the emergence of cultural dialects has been regarded as unlikely for species with more variable song, such as the zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…(2018) and Wang et al. (2021) used multiple Raspberry Pi's as part of a long‐term, automated recording and monitoring system of groups of birds in outdoor aviaries. Finally, Heuschele et al.…”
Section: Overview Of Applications Across the Biological Domainmentioning
confidence: 99%
“…(2018) and Wang et al. (2021) used multiple Raspberry Pi's as part of a long‐term, automated recording and monitoring system of groups of birds in outdoor aviaries. Finally, Heuschele et al.…”
Section: Overview Of Applications Across the Biological Domainmentioning
confidence: 99%
“…Albeit that the songs of these birds shared significantly more elements with the tutor (father) than unfamiliar control songs (unfamiliar brothers' songs: 53% ± 10%; unfamiliar songs: 19% ± 11%), they were not preferred. This is surprising given that other studies in the zebra finch reported preferences for (foster) brothers' songs and peer group songs (Holveck and Riebel, 2010;Honarmand et al, 2015) or microdialects (Wang et al, 2022). However, sample sizes in Riebel and Smallegange (2003) were small overall (18 birds from only four families) so that the different learning outcomes in tutees from different tutors (Tchernichovski et al, 2021) could have had an unduly influence.…”
Section: Discussionmentioning
confidence: 90%
“…The 4 populations have been maintained in separate aviaries (without visual and with limited auditory contact). When birds from 2 different populations (combining S with B and K with M) were brought together in the same breeding aviary, they formed social pairs that were predominantly assortative with regard to population (87% assortative pairs), despite the fact that opposite-sex individuals were unfamiliar with each other ([ 52 ]; see also [ 62 ]). To find out whether this assortative mating took place because of genetic (e.g., body size) or cultural (e.g., song) differences, we produced an offspring generation (“F1”) in which half of the birds were cross-fostered between populations (between S and B or between K and M) and half of the birds were cross-fostered within populations.…”
Section: Methodsmentioning
confidence: 99%
“…One practical obstacle is that the costs of choosiness can only be measured if one finds a sufficiently strong preference that will be reliably expressed by the choosing sex. In zebra finches, a socially monogamous bird that forms lifelong pair bonds, females reliably prefer (unfamiliar) males that have learned their song in the same population in which females grew up, over males with song from a different population [ 52 ]. Working with 4 independent captive populations (2 domesticated and 2 recently wild derived), we used cross-fostering of eggs between populations to produce 2 different cultural lineages (A and B) within each population that differ only in their song dialects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation